H. pylori May Not Be Associated with Iron Deficiency Anemia in Patients with Normal Gastrointestinal Tract Endoscopy Results - Tayyibe Saler; Şakir Özgür Keşkek; Sibel Kırk; Süleyman Ahbab; Gülay Ortoğlu (Advances in Hematology)
Background. The aim of this study was to investigate the association between iron deficiency anemia and H. pylori in patients with normal gastrointestinal tract endoscopy results. Materials and Methods. A total of 117 male patients with normal gastrointestinal tract endoscopy results were included in this retrospective study. The study and control groups included 69 and 48 patients with and without iron deficiency anemia, respectively. The prevalence of H. pylori, the number of RBCs, and the levels of HGB, HTC, MCV, iron, and ferritin were calculated and compared. Results. There was no statistically significant difference found between the groups according to the prevalence of H. pylori (65.2% versus 64.6%, P=0.896). Additionally, the levels of RBCs, HGB, HTC, MCV, iron, and ferritin in the patients in the study group were lower than those in the control group (P<0.05). Finally, there was no association between iron deficiency anemia and H. pylori (OR 1.02, Cl 95% 0.47–2.22, and P=0.943). Conclusion. H. pylori is not associated with iron deficiency anemia in male patients with normal gastrointestinal tract endoscopy results.